Phytohormones and Beneficial Microbes: Essential Components for Plants to Balance Stress and Fitness - Egamberdieva, Dilfuza; Wirth, Stephan J.; Alqarawi, Abdulaziz A.; Abd_Allah, Elsayed F.; Hashem, Abeer (Frontiers in Microbiology, 2017)
Plants are subjected to various abiotic stresses, such as drought, extreme temperature, salinity, and heavy metals. Abiotic stresses have negative impact on the physiology and morphology of plants through defects in the genetic regulation of cellular pathways. Plants employ several tolerance mechanisms and pathways to avert the effects of stresses that are triggered whenever alterations in metabolism are encountered. Phytohormones are among the most important growth regulators; they are known for having a prominent impact on plant metabolism, and additionally, they play a vital role in the stimulation of plant defence response mechanisms against stresses. Exogenous phytohormone supplementation has been adopted to improve growth and metabolism under stress conditions. Recent investigations have shown that phytohormones produced by root-associated microbes may prove to be important metabolic engineering targets for inducing host tolerance to abiotic stresses. Phytohormone biosynthetic pathways have been identified using several genetic and biochemical methods, and numerous reviews are currently available on this topic. Here, we review current knowledge on the function of phytohormones involved in the improvement of abiotic stress tolerance and defence response in plants exposed to different stressors. We focus on recent successes in identifying the roles of microbial phytohormones that induce stress tolerance, especially in crop plants. In doing so, this review highlights important plant morpho-physiological traits that can be exploited to identify the positive effects of phytohormones on stress tolerance. This review will therefore be helpful to plant physiologists and agricultural microbiologists in designing strategies and tools for the development of broad spectrum microbial inoculants supporting sustainable crop production under hostile environments.